Systemic Intervention - Midgley, Gerald. author. aut Link
XIV, 447 p.
Keywords: This book aims to rethink systemic intervention to enhance its relevance for supporting social change in the 21st Century. It offers a new systems philosophy and methodology, focusing upon the fundamental importance of exploring value and boundary judgements as part of the intervention process. A pluralist practice is also promoted, and the reader learns how s/he can draw upon a wide variety of theories and methods to maximise flexibility and responsiveness during interventions. Four detailed examples of the practice of systemic intervention are also provided, each of which is used to illustrate a different aspect of the methodology outlined in the book.